Memperkuat Integrasi Nasional Dengan Memanfaatkan Generasi Muda dan Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Rifqi Ghaida Sakhi; Fatma Ulfatun Najicha (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Integration is a process that has been going on since ancient times until now. This process has important continuities and has a significant impact on humans and society as a whole. This article aims to assess whether a sense of nationalism still exists in today's generation. The method used is a qualitative study based on literature studies with data collection from relevant journals with the title "Strengthening National Integration through National Generation and Technology in Citizenship Education Learning." From the results of this study, it can be concluded that the importance of the spirit of nationalism must still be strengthened in the nation's generations. The current era is marked by rapid technological progress throughout the world, so it is increasingly important to remind each other to keep the spirit of struggle high. If not, a national integration crisis could arise in Indonesia in the 21st century. Therefore, technology can be an effective tool in building strong integration in various fields through Citizenship Education (PKN) learning.